Gold nanoparticles physicochemically bonded onto tungsten disulfide nanosheet edges exhibit augmented plasmon damping - Forcherio, Gregory T.; Backes, Claudia; Vaynzof, Yana (AIP Advances, 2017)
Augmented plasmonic damping of dipole-resonant gold (Au) nanoparticles (NP) physicochemically bonded onto edges of tungsten disulfide (WS2) nanosheets, ostensibly due to hot electron injection, is quantified using electron energy loss spectroscopy (EELS). EELS allows single-particle spatial resolution. A measured 0.23 eV bandwidth expansion of the localized surface plasmon resonance upon covalent bonding of 20 nm AuNP to WS2 edges was deemed significant by Welch’s t-test. Approximately 0.19 eV of the measured 0.23 eV expansion went beyond conventional radiative and nonradiative damping mechanisms according to discrete dipole models, ostensibly indicating emergence of hot electron transport from AuNP into the WS2. A quantum efficiency of up to 11±5% spanning a 7 fs transfer process across the optimized AuNP-TMD ohmic junction is conservatively calculated. Putative hot electron transport for AuNP physicochemically bonded to TMD edges exceeded that for AuNP physically deposited onto the TMD basal plane. This arose from contributions due to (i) direct physicochemical bond between AuNP and WS2; (ii) AuNP deposition at TMD edge sites; and (iii) lower intrinsic Schottky barrier. This improves understanding of photo-induced doping of TMD by metal NP which could benefit emerging catalytic and optoelectronic applications.